Behavioral interventions to benefit cognition (Intervenciones cognitivas para beneficiar la cognición) - Jennifer L. Etnier; Chia-Hao Shih; Aaron Piepmeier (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
With the growing population of older adults, the identification of treatment strategies to prevent or ameliorate age-related cognitive decline has been an important topic in recent years. After reviewing cross-sectional, longitudinal, and experimentally designed studies, as well as evidence from narrative and meta-analytic reviews, the authors concluded that behavioral approaches such as physical activity, cognitive training, and dietary interventions show promising results. In addition, given the likelihood that multiple underlying mechanisms support cognitive function, research is currently focusing on how to combine lifestyle factors into multi-component interventions to generate greater and more meaningful effects. Though evidence for these enhanced benefits exists from animal studies, few multi-component studies have been performed with humans. However, the findings from these studies are promising and a continued pursuit of multi-component behavioral interventions to benefit cognitive performance is warranted. Given the world’s aging population and accompanying age-related health issues such as cognitive decline and dementia, future research should focus on understanding the biological mechanisms responsible for these effects in order to allow for the development of behavioral lifestyle prescriptions to benefit cognitive performance. Keywords. aging, cognitive function, exercise intervention, oxidative stress, cognitive engagement.